CI Camelopardalis: The first sgB[e]-high mass X-ray binary twenty years on: A supernova imposter in our own Galaxy? - Bartlett, E. S.; Clark, J. S.; Negueruela, I. (Astronomy and astrophysics (Berlin), 2019)
Context. The Galactic supergiant B[e] star CI Camelopardalis (CI Cam) was the first sgB[e] star detected during an X-ray outburst. The star brightened to ∼2 Crab in the X-ray regime (∼5 × 10−8 ergs cm−2 s−1 in the 2–25 keV range) within hours before decaying to a quiescent level in less than two weeks, clearly indicative of binarity. Since the outburst of CI Cam, several sgB[e] stars have been identified as X-ray overluminous for a single star (i.e. LX >  10−7 Lbol). This small population has recently expanded to include two ultra luminous X-ray sources (ULX), Holmberg II X-1 and NGC 300 ULX-1/supernova imposter SN2010da. Aims. Since the discovery of X-ray emission from CI Cam, there have been many developments in the field of massive binary evolution. In light of the recent inclusion of two ULXs in the population of X-ray bright sgB[e] stars, we revisit CI Cam to investigate its behaviour over several timescales and shed further light on the nature of the compact object in the system, its X-ray outburst in 1998 and the binary system parameters. Methods. We analysed archival XMM-Newton EPIC-pn spectra and light curves along with new data from Swift and NuSTAR. We also present high-resolution (R ∼ 85 000) Mercator/HERMES optical spectra, including a spectrum taken 1.02 days after our NuSTAR observation. Results. Despite being in quiescence, CI Cam is highly X-ray variable on timescales of days, both in terms of total integrated flux and spectral shape. We interpret these variations by invoking the presence of an accreting compact companion immersed in a dense, highly structured, aspherical circumstellar envelope. The differences in the accretion flux and circumstellar extinction represent either changes in this environment, triggered by variable mass loss from the star, or the local conditions to the accretor due to its orbital motion. We find no evidence for pulsations in the X-ray light curve. Conclusions. CI Cam has many similarities with SN2010da across mid-IR, optical and X-ray wavelengths suggesting that, subject to distance determination for CI Cam, if CI Cam was located in an external galaxy its 1998 outburst would have led to a classification as a supernova imposter.